2016
DOI: 10.1186/s12879-016-1683-z
|View full text |Cite
|
Sign up to set email alerts
|

Twin epidemics of new and prevalent hepatitis C infections in Canada: BC Hepatitis Testers Cohort

Abstract: BackgroundWe characterized the twin epidemics of new and prevalent hepatitis C virus (HCV) infections in British Columbia, Canada to inform prevention, care and treatment programs.MethodsThe BC Hepatitis Testers Cohort (BC-HTC) includes individuals tested for HCV, HIV or reported as a case of HBV, HCV, HIV or active TB between 1990–2013 linked with data on their medical visits, hospitalizations, cancers, prescription drugs and mortality. Prevalent infection was defined as being anti-HCV positive at first test.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
67
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 46 publications
(70 citation statements)
references
References 18 publications
3
67
0
Order By: Relevance
“…Although literature and national modeling estimates suggest that 20–44% of HCV infections remain undiagnosed in Canada (Trubnikov et al, 2014), because of high HCV testing rates in BC and declining positivity among baby boomers (born 1945–64), (Janjua et al, 2016b, Consolacion et al, 2015) we used an undiagnosed estimate of 25%, bringing the anti-HCV prevalence in BC in 2012 to 73,203(1.6% of the population). Of these, 56% (40,656) had at least one HCV RNA test; 36% (26,300) had genotype testing; 12% (8532) had been dispensed treatment; and 7% (5197) were estimated to have achieved SVR (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although literature and national modeling estimates suggest that 20–44% of HCV infections remain undiagnosed in Canada (Trubnikov et al, 2014), because of high HCV testing rates in BC and declining positivity among baby boomers (born 1945–64), (Janjua et al, 2016b, Consolacion et al, 2015) we used an undiagnosed estimate of 25%, bringing the anti-HCV prevalence in BC in 2012 to 73,203(1.6% of the population). Of these, 56% (40,656) had at least one HCV RNA test; 36% (26,300) had genotype testing; 12% (8532) had been dispensed treatment; and 7% (5197) were estimated to have achieved SVR (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The BC-HTC construction and data linkage has been described elsewhere (Janjua et al, 2016a, Janjua et al, 2016b). Briefly, the BC-HTC includes all individuals tested for HCV or HIV, or reported as a case of HBV, HCV, HIV or active tuberculosis (TB) in BC between 1990 and 2013 linked with data on medical visits, hospitalizations, cancers, prescription drugs, and deaths (BC Vital Statistics Agency, 2014, British Columbia Ministry of Health, 2014a, British Columbia Ministry of Health, 2014b, British Columbia Ministry of Health, 2014c, British Columbia Ministry of Health, 2014d, British Columbia Ministry of Health, 2014e).…”
Section: Methodsmentioning
confidence: 99%
“…All prescriptions dispensed in BC are recorded in a centralized system called PharmaNet, irrespective of the payer. Detailed characteristics of the cohort, including linkage and related data, are presented elsewhere 15,16. Data linkages were approved by the data stewards of the BCCDC, BCCDC-PHL, BC Ministry of Health, BC Vital Statistics Agency, and BC Cancer Registry.…”
Section: Methodsmentioning
confidence: 99%
“…This stratification was done because our previous research showed differences in characteristics between these two populations 16. HCV + -prevalent and HCV + seroconverters are different in terms of demographic and risk factors.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation